2011
DOI: 10.1111/j.1470-6431.2010.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in knowledge and attitude regarding breastfeeding

Abstract: The literature presented evidence that the opinions and attitudes of the father or male partner towards breastfeeding have a strong positive correlation with breastfeeding initiation and duration. Men are also found less knowledgeable about breastfeeding and are more positive towards formula feeding than women. Using a survey of college-aged men and women, this study provides in-depth understanding of gender differences in knowledge and attitude regarding breastfeeding. The Infant Feeding Knowledge Test and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
3
9
1
Order By: Relevance
“…Our study showed the negative attitudes of fathers regarding breastfeeding in public and regarding the convenience of it, Jordanian fathers tend to consider breastfeeding in public as a conflict and this might be related to the conservative nature of Jordanian society. Findings are nearly in consistent with other studies in which Breastfeeding in public is still considered as a problem worldwide (Laantera et al, 2010;Chang, Valliant and Bomba, 2012;Mitchell-Box and Braun, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed the negative attitudes of fathers regarding breastfeeding in public and regarding the convenience of it, Jordanian fathers tend to consider breastfeeding in public as a conflict and this might be related to the conservative nature of Jordanian society. Findings are nearly in consistent with other studies in which Breastfeeding in public is still considered as a problem worldwide (Laantera et al, 2010;Chang, Valliant and Bomba, 2012;Mitchell-Box and Braun, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies showed the positive attitudes of the fathers regarding breastfeeding (Avery and Magnus, 2011;Tas-pınar et al, 2012) while other studies showed a fathers` negative attitudes regarding breastfeeding in public (Laantera et al, 2010;Chang, Valliant and Bomba, 2012) and regarding the convenience of it ( Mitchell-Box and Braun, 2012). Moreover, a study in Egypt showed the passive breastfeeding attitudes among the participants including males (Ahmed and EL-Guindy, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these concerns, it was notable to find that, although females were more likely than males to report breastfeeding exposure, male students were less likely to express concerns with such exposure and were more likely to intend to [support a partner to] breastfeed a future child. The more positive attitudes found among Chinese males, compared to Chinese females, are in contrast with those reported by Korean, US, and Canadian students, 22,24,28 where either there were no differences by gender or females reported more positive attitudes. This finding possibly becomes more important when considering that more than half of this sample expressed the expectation of father involvement in the infant feeding decision.…”
Section: Discussioncontrasting
confidence: 86%
“…19 Therefore, understanding young adults’ breastfeeding knowledge, attitudes, prior exposures, and future intent may reveal critical gaps that could lead to targeted intervention. Globally, there have been only a small number of studies investigating these factors among youth: in the United States, 20-22 Hong Kong, 23 Canada, 24-26 the United Kingdom, 27 Korea, 28 Kuwait, 29 and Australia. 30 To the authors’ knowledge, this is the first study exploring these concepts among young adults in Mainland China.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, this article suggests several areas for future investigation, some of which are already of increasing importance to consumer research examining relationships (Birtalan, Neulinger, Rácz, & Bárdos, 2020; Chang, Valliant, & Bomba, 2012; Ritchie, 2007; Viholainen, Kylkilahti, Autio, & Toppinen, 2020). It will be imperative for additional research to turn more attention to the object itself.…”
Section: Conclusion Limitations and Further Researchmentioning
confidence: 97%